Sport and public TV in Brazil: the TV Brasil, the audience and the broadcasts of Brazilian Série C Championship - Cestari, Priscila Eugênia Trevisan (2017)
TV Brazil is a public broadcaster that belongs to Brazil Communications Company (EBC). It was created to implement the Communication Public System in the country. Since 2013, the station broadcasts Brazilian Série C Championship Football matches. The purpose of this article is to analyze if the issuer meets, through sport, the role for which it was created. For it, we used the concepts of audience, media culture and news value and conducted a qualitative, exploratory and descriptive research with the analysis of internal documents of the issuer and conducting interviews about the theme. The study aims to contribute reflections on the existing processes of management of sport and public communication in Brazil. So we try to verify that the broadcaster fulfills its mission to training and strengthening of citizenship and national identity or whether it is just ruled in their relationship with the sport, from the perspective of commercial audience.